A Comparative Analysis of Present Land Use in Two Typical Areas of West Indian Arid Zone - A Case Study - Sen, Amal Kumar; Lal, Gheesa (Annals of Arid Zone, 2016)
To asses the use misuse of lands and to visulaise the land use problems of the Indian Arid Zone, land utilisation surveys have been conducted in the Bilara (rocky desert) and Shergarh (sandy desert) tehsils. The survey and mapping works have been based mailnly on aerial photo-interpretation. The present land use pattern of the tehdilisl has been described A comparative analysis of the results in the both the tehsils has been attempted. This has enabled us to draw out the problems of land use in different environmental setups of the arid zone. The stud reflects on some problems like detailed sols and land capability surveys on waste land reclamation of ' Marginal' land; correct estimation of pasture land etc, which require further consideration.